A clinician's guide to mental health conditions in adults with autism spectrum disorders : assessment and interventions - Chaplin, Ed, 1945-; Spain, Debbie; McCarthy, Jane Mary (Jessica Kingsley Publishers, 2020)
"This comprehensive and much-needed guide addresses the issues faced by clinicians in assessing and treating the range of mental health conditions, which can affect adults with Autism Spectrum Disorder (ASD). Its particular focus on adults fills a notable gap in the ASD professional literature, with an extensive array of contributors from across the psychology and healthcare professions. Covering a wide variety of common co-occurring mental health conditions including mood disorders, anxiety, psychosis, OCD, personality disorders, and eating disorders, this guide also explores broader issues to do with promoting positive mental health and wellbeing. Authoritative and detailed, this is an essential resource for all clinicians and professionals looking to understand and tailor their approach to mental health in autistic adults, and the need for specific methods and strategies to enhance assessment and treatment"--Publisher's description